GE_GERICHTE A/3140/2024 vom 28. Mai 2025 - GE Cour de justice (2025)
PISCINE;MOTIVATION SOMMAIRE;GARANTIE DE LA PROPRIÉTÉ;PLAN DIRECTEUR;ÉMOLUMENT;PROPORTIONNALITÉ | Cst.29.al2; LCI.59.al3bis; Cst.26.al1; LaLAT.10.al8; LCI.154; RCI.254; RCI.257